The role of religious faith in marital satisfaction - Tevaraji, P. (Animo Repository, 1988)
The purpose of this study was to show the role of religious faith in marital satisfaction. The study was viewed from the psychological, pastoral and scriptural points of view. The factors identified for religious faith were knowledge, religious experience, religious beliefs, church attendance and involvement. For marital satisfaction, the factors were companionship, sexual fulfillment and parenting children. The following hypotheses were presented. Firstly, there is a significant intercorrelation among the three areas of marital satisfaction and between each of these areas and overall marital satisfaction. Secondly, there is a significant intercorrelation among the five areas of religious faith and between each of these areas and overall religious faith. Thirdly, there is a significant correlation between the couples' marital satisfaction (overall and in three areas) and religious faith (overall and in five areas). The study utilized the descriptive research design using the survey technique, and data were collected by the use of two questionnaires (religious faith questionnaire and marital faith questionnaire) prepared by the researcher. The number of subjects who responded was 88 (76 percent of the couples chosen by purposive sampling). The couples were Filipino Christians, from different socio-economic backgrounds, from different parts of Metro Manila, and from different age groups able to speak and write English married for at least two years and had at least two children. The Pearson product moment correlation was computed to test each of the hypotheses. The findings of the study revealed that the respondents are quite strong in their religious faith level (overall mean = 4.19), and are also quite satisfied in their marital satisfaction level (overall mean = 4.07). Statistical analyses of the data showed that there were significant intercorrelations among the three areas of marital satisfaction (r's = .66 to .70 p .01) and between each of these areas and overall marital satisfaction (r's The r